Uji Efektivitas Ekstrak Daun Cengkeh (Syzygium Aromaticum L.) Terhadap Phytophthora Palmivora Penyebab Penyakit Busuk Buah Kakao (Theobroma Cacao L.) - DEWI, NI LUH PUTU SONIA SAVITA; SUPRAPTA, DEWA NGURAH; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Effectiveness of Clove Leaf Extract (Syzygium aromaticum L.) against Phytophthora palmivora the Cause of Cocoa Fruit Rot (Theobroma cacao L.) Cocoa fruit rot caused by Phytophthora palmivora is one of the main diseases that can greatly reduce the yield of cocoa production in the world. Therefore it is necessary to control the disease in an environmentally friendly way. One of which is using botanical pesticides. Clove leaf is one of the plants which extract can be used as a fungicide. This study aimed to examine the effectiveness of clove leaf extract on P. palmivora the cause of cocoa fruit rot. MIC test and colony test was done using 10 extract concentrations namely 0,1; 0,2; 0,3; 0,4; 0,5; 0,6; 0,7; 0,8; 0,9; 1,0 and 0,0% (control). The in vivo test uses 6 extract concentrations of 0,5; 0,6; 0,7; 0,8; 0,9; 1,0 and 0,0% (control). The results showed the MIC (minimum inhibitory concentration) of clove leaf extract to suppress the growth of P. palmivora was 0.5% which means it is feasible to be used as a botanical pesticide. Under in vivo condition, clove leaf extract inhibited the growth of fungal colonies and infection and can be used as fungicide to suppress the growth of P. palmivora. The extract concentration of 1% prevented the damage of cocoa fruit caused by P. palmivora by 100%.